Video Presentation about Menarche and the Impact on Student Knowledge Level of Elementary and Islamic Primary School - Asasih Villasari; Sentot Imam Suprapto; Indasah Indasah (Journal for Quality in Public Health, 2021)
Background: Some people feel it is taboo to talk about menstrual problems in their families, so that early adolescents do not have sufficient knowledge and attitudes about the physical and psychological changes related to menarche. Mental readiness is needed before menarche because feelings of anxiety and fear will arise, besides that, there is also a lack of knowledge about the self-care needed during menstruation. Mental readiness is needed before menarche because feelings of anxiety and fear will arise, besides that there is also a lack of knowledge about the self-care needed during menstruation. Method: The research design used the Quasy Expriement Study. The population was 152 students from Elementary School 02 and Islamic Primary School 01. With simple random sampling technique, it was obtained 112 respondents. The research instrument was a questionnaire. Result: The results of the study were analyzed by using logistic regression. The results of the study showed that the significance of health education was 0.000 <0.05, so that there was an effect of health education using video on student anxiety levels with an influence coefficient value of 2.756. Meanwhile, for knowledge with a significant value of 0.028 <0.05, there is an effect of knowledge with the level of anxiety with an influence coefficient value of 1.354. Conclusion:The results of the analysis show that there is an effect of video exposure about menarche on the level of knowledge and anxiety levels in Elementary School 02 and Islamic Primary School 01 grade 4, grade 5 and grade 6 students in Gemarang, Madiun Regency.